THE POSITION AND AUTHORITY OF THE ELECTION SUPERVISORY BOARD IN INDONESIAN CONSTITUTIONAL SYSTEM - Uu Nurul Huda (Universitas Kuningan, 2019)
The institutional arrangement of election organizers through the strengthening of the Election Supervisory Board is regulated in Law No. 7 of 2017 concerning General Elections. One of these arrangements is related to the strengthening of the position and authority of the Election Supervisory Board in handling election violations. This study aims to find out the position of the Election Supervisory Board in Indonesian administration system and to analyze the authority of the Election Supervisory Board in handling election violations. The method used in this study was a normative juridical method by employing library research. The collected data were then analyzed qualitatively. The results showed that the position of the Election Supervisory Board in Indonesian administration system is one of the state election organizers in which its position is equal to the General Election Commission and the Honorary Council of Election Committee. Meanwhile, the authorities of the Election Supervisory Board include; receiving and following up on reports relating to alleged violations in the implementation of legislations governing general election; examining, analyzing and deciding on violations in general election administration; examining, analyzing and deciding on violations of money politics; and receiving, examining, mediating or adjudicating, and deciding upon the resolution of election process disputes. Based on these authorities, the Election Supervisory Board as an institution is a super-body general election organizer in handling election violations. Penataan kelembagaan penyelenggara pemilu melalui penguatan Badan Pengawas Pemilihan Umum telah diatur Undang-Undang Nomor 7 Tahun 2017 tentang Pemilihan Umum. Penataan tersebut salah satunya berkaitan dengan penguatan kedudukan dan wewenang Badan Pengawas Pemilihan Umum dalam penanganan pelanggaran pemilu. Tujuan penelitian ini adalah untuk mengetahui dan menganalisis bagaimana kedudukan Badan Pengawas Pemilihan Umum dalam sistem ketatanegaraan Indoensia, dan untuk mengetahui serta menganalisis wewenang Badan Pengawas Pemilihan Umum dalam penanganan pelanggaran pemilu. Metode penelitian yang digunakan adalah yuridis normatif dengan pendekatan penelitian studi kepustakaan dan analisisnya menggunakan deskriptif analisis. Hasil penelitian menunjukkan bahwa kedudukan Badan Pengawas Pemilihan Umum dalam sistem ketatanegaraan merupakan salah satu lembaga negara penyelenggara pemilu, di samping Komisi Pemilihan Umun dan Dewan Kehormatan Penyelenggara Pemilihan Umum. Adapun wewenang Badan Pengawas Pemilihan Umum di antaranya“menerima dan menindaklanjuti laporan yang berkaitan dengan dugaan adanya pelanggaran terhadap pelaksanaan peraturan perundang-undangan yang mengatur mengenai Pemilu; memeriksa, mengkaji, dan memutus pelanggaran administrasi Pemilu; memeriksa, mengkaji, dan memutus pelanggaran politik uang; menerima, memeriksa, memediasi atau mengadjudikasi, dan memutus penyelesaian sengketa proses Pemilu.”Berdasarkan wewenang tersebut, Badan Pengawas Pemilihan Umum secara kelembagaan merupakan lembaga penyelenggara pemilu yang superbody dalam penanganan pelanggaran pemilu.